Вплив легалізації грального бізнесу на розвиток готельної індустрії - Кирпіченкова, Оксана Миколаївна; Литвинець, Лариса Федорівна; Ущаповський, Артем Олегович (My University, 2023)
Стаття присвячена проблемі розвитку готельного бізнесу України завдяки легалізації азартних ігор. Це було зроблено з метою наповнити бюджет України значними коштами, стимулювати розвиток готельного, ресторанного бізнесу. Згідно реєстрів, де наведена інформація щодо наявності у суб'єкта господарювання права на провадження діяльності з організації та проведення азартних ігор у гральних закладах казино на сьогоднішній день в Україні функціонує вісім крупних операторів, що зареєстрували свої бренди азартних ігор. Вони комбінують в одному закладі зали для гри в рулетку, ігор в карти та зали гральних автоматів, де використовують різні види грального обладнання. Ще дванадцять операторів проваджують діяльність з ор-ганізації та проведення азартних ігор у залах гральних автоматів. Вони створили розгалужену мережу залів гральних автоматів при готелях , що охоплює всі великі міста України. Отже азартні ігри не втрачають своєї актуальності, вони однією з рушійних сил туризму внутрішнього та світового, що позитивно впливає на роз-виток готельної сфери. The article is devoted to the problem of the development of the hotel business in Ukraine thanks to the legaliza-tion of gambling. The ban on the gambling business showed that there is a demand for gambling establishments. During the period when gambling was prohibited on the territory of Ukraine, every year law enforcement agencies exposed hundreds of illegal establishments: casinos, poker halls, slot machine halls, etc. The legalization of the gambling business took place to strengthen the development of the hotel and restaurant business. business Accord-ing to the registers, which provide information about the business entity's right to organize and conduct gambling activities in casino gambling establishments, eight large operators that have registered their gambling brands are operating in Ukraine today. They combine in one institution rooms for playing roulette, playing cards, and rooms for slot machines, where different types of gaming equipment are used. This helps to attract more guests with different tastes. Another twelve operators are involved in the organization and conduct of gambling in slot machine halls. They created an extensive network of gaming machine halls at hotels, covering all major cities of Ukraine. Based on the results of the analysis of the given data, the following conclusions can be drawn. Gambling does not lose its relevance and is one of the driving forces of domestic and international tourism. This has a positive effect on the development of the hotel industry. But with the development of the gambling business, the expected revenues were not received. Therefore, there is a need to further improve the legal framework for taxation of the gaming business and strengthen state control.
Keywords: готель; гемблінг; ігровий туризм; гральний бізнес; організація азартних ігор; казино; hotel; gambling; game tourism; gambling business; organization of gambling; casino; кафедра готельно-ресторанної справи